Clear Your Mind, Ready Your Body For Sleep: Efektivitas Teknik Mindfulness Terhadap Kualitas Tidur Mahasiswa - Shabilla Yovanda Lukman; Hanifah Salma Putri; Izmi Ayuning Dita; Tuti Rahmi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to examine the effectiveness of the mindfulness technique in improving the sleep quality of university students experiencing sleep disturbances. The study employed a quantitative approach using a Randomized Pretest–Posttest Control Group Design. The participants consisted of 20 students from the Bukittinggi Branch Campus of Universitas Negeri Padang, randomly assigned to an experimental group and a control group, with 10 participants in each group. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and analyzed with the Mann–Whitney U test using IBM SPSS. The normality test indicated that all data were normally distributed. The Mann–Whitney U analysis yielded an Asymp. Sig. (2-tailed) < 0.001, indicating a significant difference in sleep quality between the experimental and control groups after the intervention. These findings suggest that the mindfulness technique is effective in improving students' sleep quality and has the potential to serve as a non-pharmacological intervention for promoting psychological well-being in higher education settings.